2001
DOI: 10.1007/s11661-001-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of martensite content and morphology on the toughness and fatigue behavior of high-martensite dual-phase steels

Abstract: A series of high-martensite dual-phase (HMDP) steels exhibiting a 0.3 to 0.8 volume fraction of martensite (V m ), produced by intermediate quenching (IQ) of a vanadium and boron-containing microalloyed steel, have been studied for toughness and fatigue behavior to supplement the contents of a recent report by the present authors on the unusual tensile behavior of these steels. The studies included assessment of the quasi-static and dynamic fracture toughness and fatigue-crack growth (FCG) behavior of the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 20 publications
5
52
0
Order By: Relevance
“…Recently, it has been observed that dual phase steel with finer microstructure exhibits higher ductility [6]. On comparison, the result of the ductility obtained in this investigation appears to agree with previous finding.…”
Section: Tensile Propertiessupporting
confidence: 92%
See 4 more Smart Citations
“…Recently, it has been observed that dual phase steel with finer microstructure exhibits higher ductility [6]. On comparison, the result of the ductility obtained in this investigation appears to agree with previous finding.…”
Section: Tensile Propertiessupporting
confidence: 92%
“…It is widely reported [6,11] that these precipitates are formed during the reheating process to the ICA temperature. The amount of carbide precipitates …”
Section: Microstructurementioning
confidence: 99%
See 3 more Smart Citations